Diversity versus mono-cropping - Sammamma, Bidakanne (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
A farmer from Bangladesh describes crop diversity in her fields and gives the reasons tor encouraging diversity versus mono-cropping.